A Decade of Dome Growth at Mount St. Helens, 1980-90 - Swanson, Donald (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary The growth of the dacite dome at Mount St.Helens between 1980 and 1986 has been more intensively studied than that of any other dome-building eruption. The growth has been complex in detail, but remarkably regular overall. This paper summarizes some of what has been learned and provides many references to additional information. Whether dome building has ended is an open question, particularly in view of the renewed, though minor, explosive activity of late 1989and early 1990.